Adoption of alternative financing strategies to increase the diffusion of picture archiving and communication systems into the radiology marketplace - Reiner, Bruce (Springer-Verlag, 2000)
The objective of the study was to evaluate current marketplace conditions and strategies employed by major picture archiving and communication systems (PACS) vendors in the creation of alternative financing strategies, to enhance the diffusion of filmless imaging. Data were collected from the major PACS vendors in the forms of survey questionnaires and review of existing leases. Topics evaluated in the survey included current financing options available, foreseeable changes in PACS financing, role of third-party financiers, and creation of risk-sharing arrangements. Generic leases were also reviewed evaluating the presence or absence of several key variables including technology obsolescence protection, hardware/soft-ware upgrades, end-of-term options, determination of fair market value, functionality/acceptance testing, uptime guarantees, and workflow management consulting. Eight of the 10 PACS vendors surveyed participated in the data collection. The vast majority of current PACS implementations (60% to 90%) occur through direct purchase, with conventional leasing (operating or capital) accounting for only 5% to 30% of PACS installations. The majority of respondents view fee-for-lease arrangements and other forms of risk sharing as increasing importance for future PACS financing. The specific targets for such risk-sharing arrangements consist of small hospital and privately owned imaging centers. Leases currently offered range in duration from 3 to 5 years and frequently offer technology obsolescence protection with upgrades, multiple end-of-term options, and some form of acceptance testing. A number of important variables frequently omitted from leases include uptime guarantees, flexibility in changing financing or vendors, and incorporation of expected productivity/operational efficiency gains. As vendors strive to increase the penetration of PACS into the radiology marketplace, there will be a shift from conventional financing (loan or purchase) to leasing. Fee-for-use leasing and other forms of risk sharing have the greatest potential in smaller hospitals, which do not have the financial resources to pursue conventional financing options. Potential PACS customers must be cautious when entering into these alternative financing strategies, to ensure that appropriate safeguards are incorporated, in order to minimize downside risk.